From Degradation to Revitalization: The Existence of Macapat Songs Among Generation Z and Adaptive Strategies Based on Cultural Ecology in The Digital Era - Indriarto, Feri Indriarto; Sulanjari, Bambang; Alfiah, Alfiah (Kaloka Jurnal Pendidikan Bahasa dan Sastra Daerah, 2024)
The degradation of Macapat songs' existence among Generation Z represents an urgent cultural issue that has yet to be systematically examined through an integrative cultural ecology framework. This study aims to: (1) analyze the current existence of Macapat songs among Generation Z through a cultural ecology approach; (2) identify multidimensional factors causing degradation by constructing a new theoretical model; and (3) formulate adaptive revitalization strategies based on empirical research synthesis. The method employed is a Systematic Literature Review (SLR) following the PRISMA-P protocol, involving the analysis of 27 selected primary sources from 2018-2025, analyzed using Braun Clarke's (2006) thematic analysis model and synthesized through Neville's Cultural Ecology Framework. The novelty of this research lies in three contributions: (1) the construction of the Macapat Degradation-Revitalization Model (MDRM) integrating six systemic dimensions of degradation; (2) the formulation of a tiered revitalization strategy based on cultural ecology that differentiates interventions at micro, meso, and macro levels; and (3) the identification of the digital paradox as both an opportunity and a threat not yet mapped in previous literature. The findings show that the degradation of Macapat songs is multidimensional – encompassing structural-social, pedagogical, cultural-global, technology-media, policy-institutional, and family transmission dimensions – that interact synergistically to form a cultural degradation spiral. The formulated revitalization strategies comprise six adaptive components: contextual curriculum integration, creative digitalization, creative industry collaboration, local institution strengthening, policy engineering, and family transmission revitalization. This research confirms that successful revitalization of Macapat songs requires an ecological-systemic approach that moves beyond conventional preservation toward a co-evolution of tradition and modernity.